Pantoea agglomerans cutaneous infection - Nwanneka Okwundu; Jessica Mercer (Journal of Dermatology and Dermatologic Surgery, 2019)
Pantoea agglomerans is a rare Gram-negative bacterium most often implicated in plant diseases and opportunistic organ system infections in immunocompromised humans. Because P. agglomerans uncommonly causes skin infections and presents with nonspecific clinical and histological findings, dermatologic diagnosis may be delayed. Our patient had a unique skin eruption that persisted after multiple treatment regimens and was finally diagnosed as P. agglomerans cutaneous infection. It is important for clinicians to consider this uncommon skin infection in their differential diagnosis of erythematous papules and vesicles with systemic symptoms. Diagnosis is via bacterial culture as histology is usually nonspecific and may not offer a conclusive diagnosis. Risk factors that may be clues to this infection include the occupation of farming, recent hospitalization, immunosuppression, and skin compromise in the form of open wounds.